2022
DOI: 10.4014/jmb.2210.10032
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Immobilization on Copper-Magnetic Nanoparticles for Efficient Bisphenol Degradation

Abstract: Laccase activity is influenced by copper (Cu) as an inducer. In this study, laccase was immobilized on Cu and Cu-magnetic (Cu/Fe 2 O 4 ) nanoparticles (NPs) to improve enzyme stability and potential applications. The Cu/Fe 2 O 4 NPs functionally activated by 3-aminopropyltriethoxysilane and glutaraldehyde exhibited an immobilization yield and relative activity (RA) of 93.1 and 140%, respectively. Under optimized conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Patel et al. reported the covalent conjugation of laccase ( R. vernicifera ) on amine‐functionalized copper containing magnetic nanoparticles (Cu/Fe 2 O 4 NPs) with 140 % activity recovery and observed ~1.4‐fold higher V max of immobilized enzyme [17] . In the case of m‐CLEAS, Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patel et al. reported the covalent conjugation of laccase ( R. vernicifera ) on amine‐functionalized copper containing magnetic nanoparticles (Cu/Fe 2 O 4 NPs) with 140 % activity recovery and observed ~1.4‐fold higher V max of immobilized enzyme [17] . In the case of m‐CLEAS, Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Patel et al reported the covalent conjugation of laccase (R. vernicifera) on amine-functionalized copper containing magnetic nanoparticles (Cu/Fe 2 O 4 NPs) with 140 % activity recovery and observed ~1.4-fold higher V max of immobilized enzyme. [17] In the case of m-CLEAS, Kumar et al reported ~4.5fold higher catalysis of m-CLAES of laccase (T. versicolor) on MNPs resulting in 8-fold higher catalytic efficiency. [25] While other reports mentioned decreased laccase activity after immobilization on MNPs as m-CLEAS.…”
Section: Kinetic Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, magnetic nanoparticles have been researched to reuse enzymes due to their biocompatibility [ 15 ]. However, the residual activity of the immobilized enzyme can be affected by enzyme inactivation after the recycling process [ 16 ]. Numerous enzymes have been immobilized on Fe 3 O 4 , including cholesterol oxidase, laccase, amylase, lipase, and pectinase [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%